Double-signal mode based on metal–organic framework coupled cascaded nucleic acid circuits for accurate and sensitive detection of serum circulating miRNAs. Issue 31 (17th March 2020) - Zhang, Susu; Xu, Shuling; Li, Xia; Ma, Rongna; Cheng, Guiguang; Xue, Qingwang; Wang, Huaisheng
Abstract : A double-signal mode based on metal–organic framework coupled cascaded nucleic acid circuits was developed for the accurate and sensitive detection of serum circulating miRNAs. Abstract : The tough challenges for the sensitive and accurate detection of circulating miRNAs (cmiRNAs) in the peripheral blood are low abundance, and high interference from environmental or background factors or other molecules. Here, we developed a double-signal mode based on metal–organic framework coupled cascaded nucleic acid circuits for the accurate and sensitive detection of serum circulating miRNAs.